Open season - Allers, Roger; Bencich, Steve; Culton, Jill; Friedman, Ron J.; Kutcher, Ashton, 1978-; Lawrence, Martin, 1965-; Mauldin, Nat; Murdocca, Michelle; Stacchi, Anthony; Columbia Pictures; Sony Pictures Animation (Firma); Sony Pictures Entertainment, Inc. (United States : Sony Pictures Entertainment : Columbia Pictures, 2006)
La interpretación de un oso pardo que ha sido domesticado por una guarda parque de ciervos ayuda a un amigo escapar de un cazador. Cuando los dos animales escapan al bosque, se pierden y, al mismo tiempo comienza la temporada de caza. Ambos animales desarrollar un fuerte vínculo afectuoso no sólo entre sí, sino también, con los demás animales salvajes en su intento de expulsar a los cazadores del bosque.
Based on an original story by Steve Moore, John Carls.
Copyright: Sony Pictures Animation, Inc. PRV: Pre-registered PRE-000000254; music compositions & sound recordings of the compositions preexisting; treatment prev. reg. 2003, PAu2-699-818. NM: entire motion picture. DCR 2006; PUB 28Sep06; REG 28Sep06; PA1-333-139.
DISPONIBLE
Not viewed.
Sources used: copyright data sheet; copyright database; Variety Web site, review posted Sept. 28, 2006, viewed Sept. 12, 2007; Internet movie database, viewed Sept. 12, 2007; FirstSearch, OCLC 75961388, viewed Sept. 12, 2007.
Summary adapted from FirstSearch, OCLC 75961388, viewed Sept. 12, 2007.
Keywords: Caza de ciervos -- Drama -- Videograbaciones; Caza de osos -- Drama -- Videograbaciones; Comedia -- Animación -- Largometraje para televisión